Asynchronous effects of heat stress on growth rates of massive corals and damselfish in the Red Sea - Fiza Zahid; Laura Gajdzik; Keith E. Korsmeyer; Jordyn D. Cotton; Daren J. Coker; Michael L. Berumen; Thomas M. DeCarlo (PLoS ONE, 2025)
Climate change is imposing multiple stressors on marine life, leading to a restructuring of ecological communities as species exhibit differential sensitivities to these stressors. With the ocean warming and wind patterns shifting, processes that drive thermal variations in coastal regions, such as marine heatwaves and upwelling events, can change in frequency, timing, duration, and severity. These changes in environmental parameters can physiologically impact organisms residing in these habitats. Here, we investigate the synchrony of coral and reef fish responses to environmental disturbance in the Red Sea, including an unprecedented combination of heat stress and upwelling that led to mass coral bleaching in 2015. We developed cross-dated growth chronologies from otoliths of 156 individuals of two planktivorous damselfish species, Pomacentrus sulfureus and Amblyglyphidodon flavilatus, and from skeletal cores of 48 Porites spp. coral colonies. During and immediately after the 2015 upwelling and bleaching event, damselfishes exhibited a positive growth anomaly but corals displayed reduced growth. Yet, after 2015–2016, these patterns were reversed with damselfishes showing a decline in growth and corals rebounding to pre-disturbance growth rates. Our results reveal an asynchronous response between corals and reef fish, with corals succumbing to the direct effects of heat stress, and then quickly recovering when the heat stress subsided—at least, for those corals that survived the bleaching event. Conversely, damselfish growth temporarily benefited from the events of 2015, potentially due to the increased metabolic demand from increased temperature and increased food supply from the upwelling event, before declining over four years, possibly related to indirect effects associated with habitat degradation following coral mortality. Overall, our study highlights the increasingly complex, often asynchronous, ecological ramifications of climate extremes on the diverse species assemblages of coral reefs.